Environmental and Mechanical Evaluation of Blended Cements With High Mineral Admixture Content - Rodrigues, Anna Luiza Macachero Victor; Mendes, Álvaro Ávila Franklin; Gomes, Vanessa; Battagin, Arnaldo Forti; Saade, Marcella Ruschi Mendes; Da Silva, Maristela Gomes (Frontiers in Materials, 2022)
The synergistic effect of combining supplementary cementitious materials (SCMs) as partial substitutes for clinker improves cement properties and reduces their clinker factor and, hence, their carbon footprint. Limestone-calcined clay cement (LC3) – a family of clinker, calcined clay and limestone filler mixes – is studied worldwide for its properties equivalent to those of Portland cement. Although slag and fly ash are no longer sufficient to keep up with current commercial blended cements in the long run, these SCMs can support the development of optimized formulations for the future. By relating the environmental and the mechanical performances, the GHG emissions-intensity offers a broader assessment and selection perspective. In this paper, thirteen blended cements were evaluated: ternary, quaternary, and multi-admixture (i. e. OPC plus 4 SCMs) blends with clinker factor between 40% and 50%, composed of – in addition to calcined clay and limestone filler - blast furnace slag and fly ash. Compressive strength was measured at 3, 7, 28, 91 and 365 days. The greenhouse gases (GHG) emissions were estimated through life cycle assessment and related to the blends’ compressive strength unit. Series D cements consistently outperformed after 3 days of age, demonstrating the benefits of the synergistic effect between SCMs jointly on GHG emissions and compressive strength. Such effect enables to not only reduce the clinker factor and carbon footprint, but also the GHG emissions intensity, which relates both. This paper showed that the formulated cements, particularly those in Series D, are potential alternatives for reducing the GHG emissions, whilst preserving mechanical performance demanded by construction market practices. From a multidisciplinary analysis standpoint, durability assessments are necessary to complement the reported findings, as low clinker contents can affect the pH of the concrete’s pore solution and carbonation that ultimately lead to deterioration.